2020
DOI: 10.22452/mojem.vol8no3.5
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy of Undergraduate Students in Selected Malaysian Higher Education Institutions: A Way Forward to Policy Recommendation

Abstract: Financial literacy is an important but often ignored skill that is vital for the young. Lack of knowledge and understanding of financial literacy will directly affect the well-being of the individual. Research indicates that due to low financial literacy, individuals experience a variety of problems that are related to personal finances such as savings, investments, or old plans, credit and so on. Previous research indicates that socioeconomic factors are important determinants of financial literacy. Most yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As the results indicate, all hypotheses were accepted as the t-value was greater than 1.96. Therefore, when examined by (Kenayathulla, Nair, Rahman, & Radzi, 2020) it was demonstrated that the monetary illiterateness level among undergraduates was higher than their financial attitudes, which remained at a moderate level. This study has created a new perspective on looking at financial literacy through the branches of knowledge, behavior, and attitude.…”
Section: Study Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…As the results indicate, all hypotheses were accepted as the t-value was greater than 1.96. Therefore, when examined by (Kenayathulla, Nair, Rahman, & Radzi, 2020) it was demonstrated that the monetary illiterateness level among undergraduates was higher than their financial attitudes, which remained at a moderate level. This study has created a new perspective on looking at financial literacy through the branches of knowledge, behavior, and attitude.…”
Section: Study Findingsmentioning
confidence: 97%
“…It has been discovered that financial literacy is positively connected with people's propensity to save money. Knowledge of both fundamental and complex financial concepts, such as how to calculate interest rates, inflation rates, percentages, stock prices, and unit trusts, is referred to as financial literacy (Kenayathulla, Nair, Rahman, & Radzi, 2020). It is now globally recognized as an essential life skill as consumers must be able to differentiate between various products, services, and providers of financial products to manage their finances successfully.…”
Section: Financial Literacymentioning
confidence: 99%
“…Kimiyaghalam and Yap (2017) as well as Ibrahim et al (2009) documented no significant differences in the level of financial literacy between men and women. Kenayathulla et al (2020) studied the level of financial literacy among undergraduate students in selected public and private institutions, in the areas of financial knowledge, behaviour, and attitudes. The research also analysed whether there were differences in terms of financial literacy by socioeconomic status or by gender.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second approach used subjective measures to measure financial literacy. Respondents are required to self-rate their financial knowledge (Kenayathulla et al, 2020;Mien & Thao, 2015;Perry & Morris, 2005). Among the questions asked are whether the respondents agree with statements related to borrowing or investment.…”
Section: Financial Literacy and Its Measurementmentioning
confidence: 99%